Femoral fractures in non-accidental trauma and child abuse: biomechanical perspective and insights - di Laura Frattura, Giorgio; Cochard, Blaise; De Marco, Giacomo; Vazquez, Oscar; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
Physical abuse remains a global problem that affects children in every country, from every ethnic group, and of all social backgrounds. The fracture of an infant's femur should constitute a red flag to a pediatrician; it must be recognized, recorded, investigated, and potentially result in measures to protect that child. Certain confounding factors, such as the reported mechanism of trauma, could negatively influence the physician's appropriate and unbiased judgment. Indeed, some physically abusive parents may try to explain a femoral fracture as the result of an accidental fall from a changing table or the child's leg getting stuck in bed barriers. This narrative review aimed to provide an overview of this topic and discuss the currently available scientific evidence to better understand the biomechanical mechanisms of femur fractures in infants, thereby definitively putting an end to some popular misconceptions.